Ivabradine treatment prevents dobutamine-induced increase in heart rate in patients with acute decompensated heart failure - NADİR, AYDIN; ÇAVUŞOĞLU, YÜKSEL; MERT, KADİR UĞUR; Nadir, AYDIN; MUTLU, FEZAN; Morrad, Bektas; ULUS, TANER (My University, 2015)
Background Ivabradine is a heart rate (HR)-lowering agent acting by inhibiting the I-f-channel. Dobutamine does increase the HR and has some deleterious effects on myocardium. So, we aimed to evaluate whether ivabradine treatment blunts a dobutamine-induced increase in HR.